Immunotherapy: Reshape the Tumor Immune Microenvironment - LV, Bingzhe; Wang, Yunpeng; Ma, Dongjiang; Cheng, Wei; Liu, Jie; Yong, Tao; Chen, Hao; Wang, Chen (Frontiers in Immunology, 2022)
Tumor immune microenvironment (TIME) include tumor cells, immune cells, cytokines, etc. The interactions between these components, which are divided into anti-tumor and pro-tumor, determine the trend of anti-tumor immunity. Although the immune system can eliminate tumor through the cancer-immune cycle, tumor appear to eventually evade from immune surveillance by shaping an immunosuppressive microenvironment. Immunotherapy reshapes the TIME and restores the tumor killing ability of anti-tumor immune cells. Herein, we review the function of immune cells within TIME and discuss the contribution of current mainstream immunotherapeutic approaches to remolding TIME. Changes in the immune microenvironment in different forms under the intervention of immunotherapy can shed light on better combination treatment strategies.